1966
DOI: 10.1017/s0007485300052731
|View full text |Cite
|
Sign up to set email alerts
|

Development of a changed response in Lucilia cuprina (Wied.) to organophosphorus insecticides in New South Wales

Abstract: Since 1956, samples of Lucilia cuprina (Wied.) from many parts of New South Wales have been tested annually for signs of resistance to organophosphours insecticides, which are used there to prevent fly-strike in sheep. For tests, 0.1 μg. diazinon per fly was applied topically; this discriminating dose was twice that required to kill 100 per cent. of susceptible flies. In 1965, some of the flies in a sample from Dubbo, in central-western N.S.W., survived the discriminating dose. Sensitivity tests of the progeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In Australia, diazinon resistance was detected in 1965 in L. cuprind 13 ). It is likely that L. cuprina entered New Zealand from Australia, so it is not surprising that New Zealand strains are also resistant<S).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, diazinon resistance was detected in 1965 in L. cuprind 13 ). It is likely that L. cuprina entered New Zealand from Australia, so it is not surprising that New Zealand strains are also resistant<S).…”
Section: Discussionmentioning
confidence: 99%
“…Periodic screening tests by the New South Wales Department of Agriculture on field samples of L. cuprina for OP-resistance detected no change in response until 1965 when a survey covering many districts in N.S.W. revealed a low-order ' tolerance' to OP-insecticides (Shanahan, 1966;Shanahan & Hart, 1966). These authors concluded that the protective period was not reduced significantly by the increased tolerance as long as insecticide application was thorough.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia L . cuprina has developed resistance to representatives of several groups of insecticides including cyclodienes (dieldrin, aldrin; Shanahan, 1959), carbamates (butacarb;Hughes & McKenzie, 1987) and organophosphorus compounds (diazinon; Shanahan, 1966). One of the earliest available organophosphorus (OP) flystrike preventives was diazinon.…”
Section: Introductionmentioning
confidence: 99%